First record of the genus Kimulodes Tjeder & Hansson in West Africa with description of a new species (Neuroptera, Ascalaphidae) - (:unkn) unknown (My University, 2012)
The genus Kimulodes was described by Tjeder and Hansson (1992) to accommodate two species, Kimulodes sinuatus originally described as Helicomitus sinuatus by Kimmins (1949) and a new species they named K. angulicornis. Within the tribe Ascalaphini, this genus is characterized by the hairless genae, the absence of a tuft of hairs at the base of the forewing in males, in contrast to the African species of Ascalaphus, and the antennae of males being sinuate or sharply arched with stout tufts of hairs on the basal flagellomeres. The genus Kimulodes was known from Central and East Africa, but remained unrecorded from West Africa. The material collected by a colleague, Jean-Michel Maldes (CIRAD), during a prospecting mission in Togo in 1990 included a male of an undescribed species of Kimulodes, which is described below. Furthermore, examination of the collection of the Museum National d'Histoire Naturelle in Paris, yielded a male and a female of K. angulicornis from an unrecorded locality in the Central African Republic.
Keywords: African Research